Hubungan Pengetahuan Sanitasi dan Higiene dengan Perilaku Kesehatan Kerja Beautician di Salon Kecantikan di Kota Sukabumi - Sarinah Triastity (Jurnal Tata Rias, 2021)
Knowledge of sanitation and hygiene is a understanding of maintaining health and avoiding disease, occupational health behavior of beautician has an important role for everyone who is in the workplace so that they live healthy and free from health problems and bad influences from work. This study aims to find out the level of the relation between sanitation and hygiene knowledge with occupational health behavior of beauticians at beauty salons in Sukabumi City. This research was conducted in a beauty salon in Sukabumi City. This research method is a quantitative method, survey with a correlational approach. The population in this research were beauticians at beauty salons in Sukabumi City with a sample of 36 people drawn from 36 people in the total population. Data for variable X (sanitation and hygiene knowledge) was obtained by means of a multiple choice test. Meanwhile, the variable Y (occupational health behavior) was obtained by distributing questionnaires with a Likert scale. The results of simple linear regression testing and hypothesis testing have a correlation significance value of 0.000 < 5% significance level (0.05) with a Pearson Product Moment value of 0.624, so there is a relation between X and Y variables. Based on the results of the coefficient of determination test, it was found that the health behavior of the beautician in a beauty salon in Sukabumi City was determined by the knowledge of sanitation and hygiene of 38.94%